Croatian Public Health Governance Model Improvement - Nino Sipina (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
The goal of this paper is to present a management model that is able to restructure and govern the public health system in Croatia. Furthermore, the goal of this model is to stabilise its financial losses and ideally, turn it into a competitive business opportunity. Amoeba Management methodology, developed in Japan from 1959-1964 by Dr. Kazuo Inamori, is a representative of enterprise agile management methodology for disruptive environment improved further up today. The methodology is based on organisational unit independency and the encouragement to take financial responsibility for overall results using a “Management by All” philosophy as well as a unified product catalogue. Each unit is treated as a ”profit centre” which faces internal quality and financial competition against equivalent nation-wide units. The central enterprise function in Amoeba Management is to unify the environment, as well as to supervise and govern units to the highest degree of success in terms of outcome and competitive financial cost. The health industry in Croatia lacks proper analysis about medical product capability delivery, as well as quality and utilisation per geographical area. Therefore, any future employed health industry governance models must be able to identify these values, unify the medical product catalogue quality within a given financial budget for equivalent organisational units, and ensure their mobility. Agility, diversification and mobility should be the main governance drivers to success, which are all addressed in Amoeba Management.
Keywords: I13; G34; L33; H51; 330; restructure; governance; Public Health; Amoeba Management; disruptive; agile; equivalent unit; Medical Product Catalogue; mobility